Climate-Smart Agriculture Practices and Their Effects on Farmers' Income and Environmental Sustainability - Chiska Nova Harsela (Politeknik Siber Cerdika Internasional, 2026)
Background: Climate change poses unprecedented challenges to global agriculture, threatening food security and farmer livelihoods worldwide. Climate-smart agriculture (CSA) has emerged as a transformative approach to address these challenges through practices that enhance productivity, build resilience, and mitigate greenhouse gas emissions. Objective: This study examines the comprehensive effects of CSA practices on farmer income and environmental sustainability across diverse agricultural contexts. Methods: Utilizing a mixed-methods approach with data from 384 smallholder farmers across multiple regions, this research employs multivariate regression analysis and environmental impact assessments to evaluate CSA adoption patterns and outcomes. Results: Results demonstrate that CSA adoption significantly increases farm productivity by 28-45%, farmer income by 35-52%, and reduces greenhouse gas emissions by 18-32% compared to conventional practices. Conclusion: The study reveals positive correlations between CSA intensity and household income diversity, with particularly strong effects on resource-use efficiency and climate resilience. These findings contribute to the growing evidence base supporting CSA as a viable pathway for sustainable agricultural development and provide actionable insights for policymakers, extension services, and development practitioners seeking to promote climate-resilient farming systems.